1989
DOI: 10.1002/j.1551-8833.1989.tb03291.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and pH on the Toxicity of Monochloramine to the Asiatic Clam

Abstract: The Asiatic clam (Corbicula fluminea) has become a pest to many users of freshwater transmission systems. Monochloramine has been suggested as a biocide because it is effective and the formation of trihalomethanes is low (see the article on page 53 of this issue). Flow‐through aquariums, a laboratory incubator, and a pilot‐scale pipeline were used to show that monochloramine concentrations between 1 and 10 mg/L effectively killed juvenile clams over a wide range of water temperatures, with mortality increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Less than 5% of the TRC was measured as free residual chlorine (FRC) and the presence of high levels of NH 3 -N would strongly implicate that chloramine species comprised the majority of TRC. Monochloramine is as or more toxic to clams than free chlorine (Cameron et al, 1989b), perhaps because clams are less able to detect chloramine (Sappington, 1987). At sites 5 and 8, TRC was as high as 1.72 mg 1-'.…”
Section: Toxicity Of Stp Dischargesmentioning
confidence: 99%
See 1 more Smart Citation
“…Less than 5% of the TRC was measured as free residual chlorine (FRC) and the presence of high levels of NH 3 -N would strongly implicate that chloramine species comprised the majority of TRC. Monochloramine is as or more toxic to clams than free chlorine (Cameron et al, 1989b), perhaps because clams are less able to detect chloramine (Sappington, 1987). At sites 5 and 8, TRC was as high as 1.72 mg 1-'.…”
Section: Toxicity Of Stp Dischargesmentioning
confidence: 99%
“…Still, secondary effects of temperature in the present study, such as greater sensitivity to chlorine, ammonia, and zinc is likely. These heightened sensitivities would be associated with greater metabolic activity' at higher temperatures (Belanger et al, in review;Cameron et al, 1989b).…”
Section: Toxicity Of Stp Dischargesmentioning
confidence: 99%
“…Mortality at targets 1 and 5 mg monochloramine/L was significantly lower during winter (17-18°C) and summer (23-28°C) ( Table 2). 36 The LT50s were much lower, on average, than for other biocides, except chlorine dioxide.…”
Section: Monochloraminementioning
confidence: 89%
“…Dye studies demonstrated that 90 percent of the solution in the vials was exchanged within 1 h, ensuring rapid exposure of juvenile clams to biocides. 36 The vials were removed from the aquariums and the number of dead and alive juveniles was counted under a dissecting microscope at 3-, 12-, or 24-h intervals. The surviving clams were identified by presence of foot movement, ciliary action, or heartbeat.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation